Injury patterns and biomechanics of the athlete's shoulder - Lintner, D.; Noonan, T. J.; Kibler, B. (Clinics in Sports Medicine, 2008)
Although shoulder injury patterns vary by sport and position, overhead sports, such as baseball, swimming, tennis, and volleyball, share a common dependence on the integrity of the kinetic chain. Disruption of this critical mechanism predisposes to injury and deserves attention as the most important of the biomechanical principles required to help evaluate and manage problems of the athlete's shoulder.